Use of biological treatments in patients with hidradenitis suppurativa. (13th March 2014) - Martin‐Ezquerra, G.; Masferrer, E.; Masferrer‐Niubò, M.; Ferran, M.; Sánchez‐Regaña, M.; Collgros, H.; Bordas, X.; Notario, J.; Alsina, M.; Gil, I.; Izquierdo, N.; Aparicio, G.; et al.
Abstract Introduction Hidradenitis suppurativa (HS) is a chronic skin disease which causes a great impact in the quality of life. Multiple therapeutic options have been proposed, and recently the potential use of biological drugs in severe cases has been postulated. Material and Methods A retrospective study from seven tertiary Spanish centers reviewing the charts of patients with HS treated with biological drugs was performed. Retrieved information included epidemiological data, clinical features, pain intensity, Hurley stage, laboratory data and therapeutic outcomes. Results Nineteen patients were included in the study; 10 men (52.6%) and 9 women. Eight patients (42%) showed a Hurley severity stage II and 11 a stage III (57.8%). Adalimumab was prescribed as the first biological treatment in nine out of 19 cases (47.3%), whereas infliximab was prescribed in seven cases (36.8%), ustekinumab in two cases (10.5%) and etanercept in one (5.2%). A complete response was observed in three patients (two cases with infliximab and one case with ustekinumab), a partial improvement in 10 patients and in six patients no clinical improvement was noted. One patient referred worsening of the skin symptoms. In 6 cases, a second biological treatment was prescribed. In three of such cases, a partial improvement was noted, whereas in three cases no clinical improvement was observed. In two cases a switch to a third biological drug was indicated, with a partial improvement in one case. Discussion and Conclusions Biological drugs could be a potential and effective therapeutic option for patients with severe HS. Complete and persistent clinical responses are rarely obtained (15%) and partial responses are achieved in approximately 50% of patients. No specific markers for a therapeutic response have been identified. No definitive conclusions regarding the most effective biological drug for HS could be drawn. Higher dosage schedules seem to be associated with higher response rates. The lack of response of one particular drug does not preclude a potential efficacy to another biological treatment.